Adiposity measures and blood pressure in Chinese children and adolescents. Issue 9 (1st April 2008) - Wang, H; Necheles, J; Carnethon, M; Wang, B; Li, Z; Wang, L; Liu, X; Yang, J; Tang, G; Xing, H; Xu, X; Wang, X
Abstract : Objective: To investigate the association of adiposity measures with blood pressure (BP) in Chinese children and adolescents. Design: A cross-sectional study. Participants: 1330 boys and 1170 girls aged 6–18 years from a rural population-based cohort of twins studied in Anhui, China, 1998–2000. Outcome measures: Adiposity measures included body mass index (BMI), total body fat and trunk fat assessed by dual-energy x -ray absorptiometry. BMI was divided into fat mass index (FMI) and lean mass index (LMI) in the analysis. Major outcomes included: systolic (S) and diastolic (D) BP. Both linear and logistic regressions were performed to assess gender-specific associations between various adiposity measures and BP, with adjustment for age and height. Generalised estimating equations were used to account for intra-twin pair correlations. Results: Mean BMI and percentage body fat in children aged 6–11 years were 14.9 kg/m 2 and 9.7%, respectively; corresponding measures in children aged 12–18 years were 17.8 kg/m 2 and 14.2%. Adiposity measures were more strongly associated with SBP (p<0.05 in all age strata) than DBP (p<0.05 only in children aged 6–11 years). Both FMI (β = 1.26–2.37) and LMI (β = 1.00–1.71) are associated with SBP across age and gender strata after adjustment for age and height (p<0.05). Conclusions: These results indicate that, in this relatively lean population of Chinese children and adolescents, BP, particularly SBP, is positively associated with measures of adiposity. Of all the adiposity measures, BMI is the strongest predictor of BP.